2021
DOI: 10.1177/0971721820960252
|View full text |Cite
|
Sign up to set email alerts
|

Why Does Cancer Screening Persist Despite the Potential to Harm?

Abstract: Population screening for early-stage cancer or cancer precursors began in the mid-twentieth century, with the goal of reducing suffering from cancer illness and lengthening average life by preventing cancer deaths. Since the establishment of cancer screening, concerns have emerged that it may be doing considerable harm; despite this, screening practices have remained relatively intractable. This intractability in the face of harm is the central problematic of my analysis. I reinterpret a large study of breast,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 50 publications
0
8
0
4
Order By: Relevance
“…First, as the point of detection is moved away from the onset of symptoms, the likelihood of a negative result is increased, meaning patients will have little to gain from taking part. Further, because of the uncertainty inherent in screening, a number of subjects might receive false negative or false positive results, which could lead to significant stress, false reassurance and even suboptimal care (Carter, 2021). Finally, even if the results were accurate, it is possible that, at least for some patients, the disease might have never led to significant impairment if left undetected, meaning testing might be unwarranted and ultimately more harmful than the condition it aims to prevent (Carter, 2021).…”
Section: 'Predictive Diagnosis': Enacting Individuals and Populationsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, as the point of detection is moved away from the onset of symptoms, the likelihood of a negative result is increased, meaning patients will have little to gain from taking part. Further, because of the uncertainty inherent in screening, a number of subjects might receive false negative or false positive results, which could lead to significant stress, false reassurance and even suboptimal care (Carter, 2021). Finally, even if the results were accurate, it is possible that, at least for some patients, the disease might have never led to significant impairment if left undetected, meaning testing might be unwarranted and ultimately more harmful than the condition it aims to prevent (Carter, 2021).…”
Section: 'Predictive Diagnosis': Enacting Individuals and Populationsmentioning
confidence: 99%
“…As noted, such use of biomarker testing remains controversial, particularly among those who are not currently aware of any sign of cognitive decline, and public health bodies have repeatedly recommended against formal population screening (Owens et al., 2020; UK National Screening Committee, 2018). Yet, the introduction of potential screening technologies is often accompanied by a moral compulsion that blurs concerns about evidence of possible harms (Carter, 2021). Moreover, such use of the tools potentially represents the largest possible scope for the technology, creating new demands for testing beyond the memory clinic.…”
Section: ‘The Only Way Is Screening’: Enacting the Value For Populationsmentioning
confidence: 99%
“…Two of the interviewees emphasised the role of Patrick Forrest for breast cancer treatment in the UK; Forrest, a surgeon, produced a report that led to the introduction, in 1987, of a breast cancer screening programme aimed at women over 50 (see also Griffiths et al, 2010). Criticism of the disease regime linked to breast cancer screening has mostly focused on two points: (1) it is sometimes falsely presented as prevention, rather than early diagnosis, which improves treatment but cannot exclude relapse or metastasis (Klawiter, 2008;Sulik, 2010), and (2) it can cause overdiagnosis, subjecting patients with tumours that would never have become problematic to unnecessary treatment that causes damage potentially outweighing the benefits of early treatment (Carter, 2021;Sulik, 2010). The only interviewee to mention a downside to breast cancer screening, Dr Arthur, focused however on the increased number of women requesting breast checks outside of organised programmes, suggesting that this phenomenon, known as 'opportunistic screening', risks 'overrunning', as he said, 'the system', and suggested that GPs should more carefully select the women referred for breast cancer screening.…”
Section: Breast Cancer: a Mosaic Of Treatments For A Fragmented Diseasementioning
confidence: 99%
“…A vast amount of published work highlights the benefit of early diagnosis of breast cancer via mammography screening. In the late 20th century, screening mammography was implemented in high-income nations, based on the finding that it decreased the mortality rate from breast cancer, without proper consideration or knowledge of potential risks [ 7 ]. Additionally, mammography screening programs started before the development of hormonal therapy and other targeted therapies for breast cancer.…”
Section: Introductionmentioning
confidence: 99%